PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Sundarsi, Keksi -; Wardiningsih, Suprihatmi Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT This study aims to analyze the significance of the effect (1) leadership on employee performance, (2) communication on the performance of employees, 3) motivation on employee performance, (4), communication on the performance of employees who moderated by motivation, (5) communication on employee performance moderated by motivation. Location of research in the Department of Culture and Tourism of Surakarta. The research population is all employees amounting to 86 people with a census technique. The analysis technique uses test validity, test reliability classical assumption test, linear regression, t test, F test, the coefficient of determination and absolute difference test. The results showed that leadership had a significant influence on the performance of employees, communication has a significant influence on employee performance, motivation has a significant influence on employee performance, motivation moderated the effect of leadership on employee performance, motivation moderated the effect of communication on the performance of employees in the Department of Culture and Tourism Surakarta. Keywords: leadership, communication, motivation, performance